The Human Potential of Economic Growth and the Competitiveness of Bulgarian Economy. Economic and Social Measurements - Vladimirova, Katya (UNWE Yearbook, 2008)
The study addresses some of the most topical issues of the economic and social development from the viewpoint of globalization, European integration and the prerequisites for Bulgaria’s efficient participation in these processes – competitive economy and social security. Based on some state-of-the-art concepts of economic development and the European policies and strategies of economic and social progress the paper poses a number of questions of methodological, and mainly of political and strategic nature with regard to the openings of achieving tangible economic results for the people of Bulgaria.The author considers that there is untapped human potential for the development of economy and an increase of income. This is predetermined by the nature of macroeconomic and social policy, of underrating the possibilities of the human factor in organizations, as well as of its quality and motivation for productive work, research and innovations. Competitive production means, above all competitive work force. The evaluation of the economic performance and the qualities of the human resources should be based on the international comparisons and standards which would enable a different assessment of the performance and the possibilities that have failed to materialize.The study focuses mainly on the nature of the modern economic development, the challenges of demographic ageing and high mobility of the population, the role of the knowledge economy, the ongoing research and the quality of the human factor for the growth and competitiveness, new forms of employment and openings for a more efficient and higher-quality employment. The author argues that the policy of economic development should target a larger-scale and higher quality employment which would the basis for achieving higher social safety. Greater employment should be one of the main targets of education while its strategies should be geared to providing quality education and training of the people who not only know , but who can achieve things, who possess creative potential and motivation to contribute to a better performance of the country at large. This presupposes that increasing a highly efficient employment will become the highlight of the economic, social, educational and health policies.